2022
DOI: 10.1177/16094069221095658
|View full text |Cite
|
Sign up to set email alerts
|

Using Asynchronous Online Focus Groups to Capture Healthcare Professional Opinions

Abstract: Introduction Online data collection methods can increase study accessibility and ease the burden of data collection for participants. Asynchronous Online Focus Groups are a promising method for data collection among healthcare professionals. Methods In this article, we describe the use of, and lessons learned from conducting 19 Asynchronous Online Focus Groups across four research studies. Results We describe our experiences preparing for, recruiting for, and conducting Asynchronous Online Focus Groups. We hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The final consideration was related to both the researchers’ and the participants’ technical competence working with Teams. Navigating the technical difficulties associated with any type of virtual research modality is well documented (Halliday et al, 2021; LaForge et al, 2022; Marques et al, 2021). Using technological interventions for synchronous or asynchronous focus groups may limit the access of some participants (LaForge et al, 2022), prove difficult for older individuals to learn new functionality (Gordon et al, 2021), and pose a challenge for those with poorer typing efficacy.…”
Section: Results and Methodological Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The final consideration was related to both the researchers’ and the participants’ technical competence working with Teams. Navigating the technical difficulties associated with any type of virtual research modality is well documented (Halliday et al, 2021; LaForge et al, 2022; Marques et al, 2021). Using technological interventions for synchronous or asynchronous focus groups may limit the access of some participants (LaForge et al, 2022), prove difficult for older individuals to learn new functionality (Gordon et al, 2021), and pose a challenge for those with poorer typing efficacy.…”
Section: Results and Methodological Observationsmentioning
confidence: 99%
“…Such interactions were limited or impossible during the pandemic, leading many researchers to conduct their focus groups online (e.g., Dodds & Hess, 2020; Marques et al, 2021). The idea of facilitating focus groups online is not new (Kalbfleisch & Eckley, 2003; Morgan & Lobe, 2011; Williams et al, 2012), and resources are available for facilitating best practices in this context (Chase & Alvarez, 2000; LaForge et al, 2022). This method helps combat some barriers to traditional face-to-face focus groups such as participant drop-out, difficulty recruiting geographically diverse participants, and personality traits like shyness which limit participation (Stewart & Shamdasani, 2017; Tausch & Menold, 2016; Tuttas, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This was an important consideration, as the data collection occurred when the movements of South African citizens were restricted due to COVID-19 regulations. Asynchronous (text-based) online focus groups have been reported to improve the experience for focus group participants 17 . It has been reported that participants in asynchronous online focus groups may feel more comfortable to provide diverse opinions due to the perceived anonymity of the online format 18 .…”
Section: Data Collectionmentioning
confidence: 99%
“…Furthermore, participants are also allowed the opportunity to respond to each other. The asynchronous groups could accommodate the research participants with limited time as they could respond to the questions and add to the discussion at any time that suited them best throughout the three days 22 . Additionally, by using an online focus group, the researchers could comply with the regulations imposed to curb the COVID-19 pandemic.…”
Section: Data Collection Proceduresmentioning
confidence: 99%
“…The situation in disadvantaged communities, particularly in informal dwellings, stood in stark contrast to this image 21 . Challenges in disadvantaged communities were overcrowding, poor sanitation, lack of access to personal protective equipment such as masks 22 , and most notably, a dire lack of food and basic supplies. This contributed to hunger riots 23 , shop looting 24 and confrontation with the South African National Defence Force (SANDF) and the South African Police Service (SAPS) 25 .…”
Section: The Implications Of the Covid-19 Lockdown On South Africansmentioning
confidence: 99%